Tolerance Towards Malaysian English As a New Variety of English - Maniam, Rukumani Devi (1998)
New Englishes have emerged all over the world and are seen as developing from what can be called the established native speaker variety. Malaysian English is a non-native variety distinct from the Standard British English. The consolidation of this variety in its present form or its continuity evolving into a form even further from its roots, depends on the attitudes of its speech community. Malaysian English has emerged in a systematic and consistent manner both in spoken and written forms. The results of the survey indicate that there is tolerance for Malaysian English both in the spoken and written mode.